Effect of Type and Size of KH550 Modified Filler on Mechanical and Tribotechnical Properties of UHMWPE Composites; AIP Conference Proceedings; Vol. 2167 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2019 (AMHS'19) - Panin S. V. Sergey Viktorovich; Huang Qitao; Kornienko L. A.; Buslovich D. Dmitry; Aleksenko V. O. Vladislav Olegovich (2019, 2019)
Title screen